Pengaruh Komitmen Afektif, Komitmen Berkelanjutan dan Komitmen Normatif Terhadap Kinerja Karyawan Pabrik Crumb Rubber Factory di PT. Pinago Utama Sugiwaras - Meisy Kuswanti; Endah Dewi Purnamasari; M. Kurniawan DP (Jurnal Bisnis, Manajemen, dan Ekonomi, 2021)
This study aims to analyze the influence of affective commitment, sustainable commitment, and normative commitment on the performance of the employees of the Crumb Rubber Factory at PT Pinago Utama Sugiwaras. The population was 250 and the final sample total was 154 which was determined deploying the Slovin formula. Data were collected through questionnaires and analyzed using the multiple linear regression method. The results of the investigation exhibit that partially each of affective commitment and sustainable commitment has a significant effect on employees' performance. Furthermore, partially normative commitment has no significant effect on employees' performance. Simultaneously, affective commitment, sustainable commitment, and normative commitment have a significant effect on employees' performance. These empirical findings can provide benefits for the Crumb Rubber Factory at PT Pinago Utama Sugiwaras. The leader of the company should pay attention to affective commitment, sustainable commitment, and normative commitment factors to optimize employees' performance